2019
DOI: 10.1002/app.47785
|View full text |Cite
|
Sign up to set email alerts
|

Improving tribological properties of phenolic resin/carbon fiber composites using m‐Si3N4@PANI core–shell particles

Abstract: Phenolic resin/carbon fiber (PF/CF) composites have good tribological properties; however, their extensive applications are limited because of the poor thermal conductivity of the phenolic resins. In this work, core‑shell particles of polyaniline‐coated (3‐aminopropyl) triethoxysilane‐modified β‐Si3N4 (m‐SiN@PANI) were used to enhance the tribological, electrical, and thermal conductivity properties of a PF/CF composite. A core‑shell particle, consisting of m‐SiN@PANI, was characterized by Fourier Transform In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…By adding h-BN@Ni powders, the microstructure of the ceramic composite was more homogeneous than that of the composite containing uncoated h-BN powders. In order to improve the poor thermal conductivity of the phenolic resin/carbon fiber (PF/CF) composites, m-Si 3 N 4 @PANI core–shell particles were synthesized [ 65 ]. The results indicated that the addition of m-Si 3 N 4 @PANI improved the thermal conductivity, electrical conductivity, COF, and wear rate of PF/CF composites effectively (thermal conductivity of 3.164 Wm −1 ·K −1 , electrical conductivity of 5.33 × 10 −6 S/m, COF of 0.1681 (reduced by 48.48%) and wear rate of 1.13 × 10 −8 mm 3 /Nm (reduced by 68.08%)).…”
Section: Applicationsmentioning
confidence: 99%
“…By adding h-BN@Ni powders, the microstructure of the ceramic composite was more homogeneous than that of the composite containing uncoated h-BN powders. In order to improve the poor thermal conductivity of the phenolic resin/carbon fiber (PF/CF) composites, m-Si 3 N 4 @PANI core–shell particles were synthesized [ 65 ]. The results indicated that the addition of m-Si 3 N 4 @PANI improved the thermal conductivity, electrical conductivity, COF, and wear rate of PF/CF composites effectively (thermal conductivity of 3.164 Wm −1 ·K −1 , electrical conductivity of 5.33 × 10 −6 S/m, COF of 0.1681 (reduced by 48.48%) and wear rate of 1.13 × 10 −8 mm 3 /Nm (reduced by 68.08%)).…”
Section: Applicationsmentioning
confidence: 99%
“…[17,18] It was considered that the strong fiberrubber interface could enhance the overall fatigue strength, and thus improve the deformation stability. [19,20] For instance, Zhang [21] incorporated basalt fibers (BFs) into the polyetheretherketone (PEEK) matrix and successfully improved tribological properties and wear resistance of as-prepared composites with addition of 2.5-7.5 phr BFs. Liang [22] prepared a high density polyethylene (HDPE)/glass fiber (GF) composites and demonstrated a reduction of 51.56% in friction coefficient under 0.4 MPa and 500 rpm as well as good wear resistance.…”
Section: Introductionmentioning
confidence: 99%